تقييم أداء بروتوكولات المصادقة في الشبكات الخلوية وفقاً لجودة الخدمة - أحمد أحمد; أماني ستيتي (Tishreen University, 2016)
نجحت شبكات LTE (Long Term Evolution) باعتبارها ذات انتاجية عالية أن تكون المظلة للشبكات اللاسلكية, مما دفع الباحثين بشدة الى دراسة وحل الثغرات الأمنية الموجودة. وكانت المصادقة المتبادلة التي اعتمدتها شبكات المحمول للتغلب على نقاط الضعف التي تُستغل لاصطياد المعِّرف الخاص بالمشترك IMSI (International Mobile Subscriber Identity) , نجح تنفيذ المصادقة المتبادلة في نظام الحزم المطّور EPS AKA (Evolved Packet System) بتعزيز الأمن على الشبكة، لكنها فشلت في تغطية نقاط الضعف التي ورثت من UMTS .إحدى هذه النقاط هو اصطياد IMSI خلال اجراء تحديد هوية المشترك .على الشبكة. حاول العديد من الباحثين على مدى السنوات الماضية، اقتراح بدائل عن EPS-AKA قادرة على ضمان مستويات عالية من الأمن وتقديم أداء جودة خدمة مقبول. في هذا البحث، سوف نقوم بتحليل SPAKA وPBKP الذي حل نقاط الضعف في EPS-AKA ، ثم سنقارن أداء جودة الخدمة لـEC-AKA وEPS AKA . البروتوكول المقترح "EC-AKA" هو المرشح الحقيقي ليحل محل المصادقة الحالية وبروتوكول اتفاق المفاتيح، لأدائه الممتاز في جميع البارامترات التي تمت دراستها. LTE's success as a high throughput, and umbrella technology for wireless networks is highly affected by the researchers' capability of solving its current security vulnerabilities. Mutual authentication was adopted by mobile networks to overcome vulnerabilities exploited by "IMSI catcher" and other active attacks. 3GPP's mutual authentication implementation in EPS AKA succeeded in enhancing the network's security, but failed to cover weaknesses inherited from its predecessor (UMTS). One of those vulnerabilities is the passive capturing of IMSIs during user identification in the Authentication and Key Agreement protocol. Many researchers tried over the past years, to propose an alternative for EPS AKA, able to ensure high levels of security and offer acceptable QoS performance. In this paper, we will crypt-analyze (SPAKA and PBKP) which was claimed to solve EPS AKA's privacy and mutual authentication weaknesses, then we will compare its QoS performance to EC-AKA and EPS AKA. Our proposed protocol "EC-AKA" is a real candidate to replace the current authentication and Key Agreement protocol, because of its excellent performance in all the studied parameters.